Study of HemolysinTitre in O Group Donors - Easmin, Fatema; Rahman, Atiar; Sultana, Nahid; Hoque, Md Mazharul; Islam, Kashfia; Shorminm, Sonia; Biswas, Jolly (Journal of Medicine, 2015)
Summary: Antibodies are globulins which are produced in response to an antigenicstimulation. The antibody that activates complement leading to cell lysis is calledhemolysin antibody. Group O donors plasma may contain potent anti A or anti-B, capable of reacting with the red cells ofgroup A, B or AB recipent and sometimescause a severe transfusion reaction. The anitbodies may take the form of high titre agglutinins or hemolysins. Patients blood group A, B or AB receiving O blood groupwith a high titre IgG anti-A or anti-B reacting at 37°C may experience a moderatetransfusion reaction resulting jaundice and progressive anaemia. Immune anti-A and anti- B are sometimes responsible for transfusion reaction. Objective: To find out the haemolysintitre of O blood group female donor. Methods: This cross sectional study was done on 100 cases of O blood group female inchild bearing age and 100 adult male was selected as control, in transfusion medicine department, BSMMU from June 2008 to May 2009. Detailed demographic and clinical findings of all subject were recorded in data collection sheet,all analysis was done using SPSS (statistical package for social science) Result: The mean age differences was found statistically significant (P<0.5) between female & male, 81(81.0%) had Rh + ve & 19% had in negative female subject. 94% hadhaemolytic test positive in female and 8% had haemolysin test positive in male subject.The mean haemolysin antibody with A cell was 2.13 ± 12.3 and with B cell was16.5±8.15. Conclusion: It is important to avoid transfusion of blood containing high titres ofimmune anti A and anti B antibodies to non O group recipients, strongly heamolytic samples have high titres of IgG, a simple screen for donor heamolysin is suggested which can decrease the risk of transfusion if platelets/plasma from donors with minor incompatibbility are used. J MEDICINE July 2015; 16 (2) : 93-96